REAKSI PASAR TERHADAP PENGUMUMAN REVERSE SPLIT PADA PERUSAHAAN GO PUBLIC DI INDONESIA - Ketut Sonya Adnyani; I Gusti Ayu Made Asri Dwija Putri (Akuntabilitas, 2014)
The purpose of this research was to determine how the market reacts because ofthe reverse split announcement. Market reaction seen from the difference in abnormal returnbefore and after the company did a reverse split announcement. This research was conductedin 2001-2012. The samples used in this study were 20 companies. This is an 11-day observationperiod. The data used in this study is a secondary data and a purposive sampling method wasused to determining samples. Technical analysis used for different test is wilcoxon signed ranktest. The results of the study shows that the market reacted to the reverse splitannouncement, marked by the difference in abnormal return before and after reverse splitDOI: 10.15408/akt.v7i2.2677